Current Treatment of Anterior Communicating Artery Aneurysms: Single Center Study - Navrátil, Ondřej; Ďuriš, Kamil; Juráň, Vilém; Svoboda, Karel; Hustý, Jakub; Hovorka, Evžen; Neuman, Eduard; Mrlian, Andrej; Smrčka, Martin (Brain sciences, 2020)
INTRODUCTION: Anterior communicating artery aneurysms (ACoAAs) are the most frequent intracranial aneurysms treated at neurosurgical departments with a vascular program. MATERIAL AND METHODS: We reviewed patients with ACoAAs in a single institution over ten years (2008-2017). The focus was on the final outcome; complications, age, and clinical condition with respect to modalities were analyzed. RESULTS: A total of 198 patients treated during this period was included in the study: 176 patients had a ruptured ACoAA and 22 had an unruptured ACoAA. Then, 127 (71%) were treated surgically and 51 (29%) by endovascular means. Out of the whole series, a good recovery occurred in 123 patients (62%), moderate disability in 11 (5.5%), severe disability in 19 (10%), vegetative state in 11 (5.5%), and death in 34 (17%). In the 157 patients (72.5%) with a subarachnoid hemorrhage (SAH), both modalities had a favorable outcome: 27.5% had an unfavorable outcome, 12% had complications in surgery versus 17.6% during endovascular treatment. No statistical difference in outcome, complications, and age was noted between modalities. Surgical treatment was more frequently adopted for patients in a better clinical condition (p ≤ 0.05). CONCLUSION: More than two thirds of the patients (72.5%) reached a favorable outcome. There was no difference in age between the treatment modalities. Risks of complications are present and specific for both modalities.